2006
DOI: 10.1111/j.1523-1739.2006.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Links between Governance and Biodiversity

Abstract: Abstract:We argue that two problems weaken the claims of those who link corruption and the exploitation of natural resources. The first is conceptual. Studies that use national level indicators of corruption fail to note that corruption comes in many fofms, at multiple levels, that may affect resource use quite differently: negatively, positively or not at all. Without a clear causal model of the mechanism by which corruption affects resources, one should treat with caution any estimated relationship between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 33 publications
(47 reference statements)
4
59
0
Order By: Relevance
“…Because the CPI is strongly associated with other factors within countries (rule of law, governance, development), it may be considered as a proxy for overall functioning of civil society of each country, and indeed development variables associated with poverty were also found to be associated with PIKE in both 2009 and 2012 [16], [33]. A previous analysis using data from the African Elephant Database [60] suggesting a link between elephant decline and poor governance was criticized [61], because latitude was a better explanatory variable and the data were collected using different methods of varying quality [4], [47]. The more recent analysis using the 2007 AED showed that the “country” variable, a complex interaction of human development and governance factors, explained elephant density very well [30].…”
Section: Discussionmentioning
confidence: 99%
“…Because the CPI is strongly associated with other factors within countries (rule of law, governance, development), it may be considered as a proxy for overall functioning of civil society of each country, and indeed development variables associated with poverty were also found to be associated with PIKE in both 2009 and 2012 [16], [33]. A previous analysis using data from the African Elephant Database [60] suggesting a link between elephant decline and poor governance was criticized [61], because latitude was a better explanatory variable and the data were collected using different methods of varying quality [4], [47]. The more recent analysis using the 2007 AED showed that the “country” variable, a complex interaction of human development and governance factors, explained elephant density very well [30].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [8], [17] have found statistical relationships between governance, or corruption, and conservation failures or biodiversity loss. These analyses have been criticised on both conceptual and statistical grounds [23]. The conceptual issue concerned how corruption is used to infer causality from an analysis which fails to account for the complex causal mechanisms that probably link it with conservation outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1950 and 2000, over 90 per cent of the major armed conflicts in the world occurred within countries containing biodiversity hotspots, and 80 per cent took place directly in biodiversity hotspot areas [39]. In general, the links between governance and the loss of biodiversity are complex [4042] but conflicts have been found to result in habitat destruction as a result of an ineffective enforcement [40,43,44]. This means that the chance of successful investments varies from place to place but this variation has not been incorporated in global prioritization templates [1,42,45].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the links between governance and the loss of biodiversity are complex [4042] but conflicts have been found to result in habitat destruction as a result of an ineffective enforcement [40,43,44]. This means that the chance of successful investments varies from place to place but this variation has not been incorporated in global prioritization templates [1,42,45]. With biodiversity hotspots concentrated in politically volatile regions, it has been recommended that the conservation community maintains continuous engagement during periods of conflict [39].…”
Section: Introductionmentioning
confidence: 99%